2021
DOI: 10.1210/jendso/bvab091
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-specific Reference Intervals for BNP and NT-pro BNP—Changes in Natriuretic Peptides Related to Pregnancy

Abstract: Background Cardiac disease is the leading cause of maternal mortality in the UK, so accurate cardiovascular diagnoses in pregnancy are essential. BNP (B-type natriuretic peptide) and NT-pro BNP (N-terminal-pro BNP) are useful clinical tools for investigating suspected peripartum cardiomyopathy but, as the pregnancy-specific reference intervals are undefined, it is uncertain how they should be interpreted in pregnant women. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…It participates in the regulation of blood pressure, blood volume, and water-salt balance. And more importantly, it can reflect cardiac function [ 29 ]. ADMA is an endogenous nitric oxide synthase inhibitor, which could induces endothelial dysfunction, and plays an important role in the occurrence and development of cardiovascular diseases for a new risk factor [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It participates in the regulation of blood pressure, blood volume, and water-salt balance. And more importantly, it can reflect cardiac function [ 29 ]. ADMA is an endogenous nitric oxide synthase inhibitor, which could induces endothelial dysfunction, and plays an important role in the occurrence and development of cardiovascular diseases for a new risk factor [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are limited normative data in pregnancy to establish a threshold for elevated NT-proBNP; thus, we used normative values for nonpregnant adults . Elevated NT-proBNP concentration was defined as a concentration greater than 125 pg/mL (nonpregnant adult threshold; to convert to nanograms per liter, multiply by 1) and greater than 200 pg/mL in sensitivity analyses (recently published pregnancy reference interval) . Results are presented as adjusted ORs with corresponding 95% CIs.…”
Section: Methodsmentioning
confidence: 97%
“…21 Elevated NT-proBNP concentration was defined as a concentration greater than 125 pg/mL (nonpregnant adult threshold; to convert to nanograms per liter, multiply by 1) and greater than 200 pg/mL in sensitivity analyses (recently published pregnancy reference interval). 22 Results are presented as adjusted ORs with corresponding 95% CIs. We used t tests for normally distributed continuous variables, Wilcoxon tests for medians, and χ 2 tests for categorical variables.…”
Section: Key Pointsmentioning
confidence: 99%
“… 15 , 23 In women free of pre-existing cardiovascular disease, studies by Dockree et al and Umazume et al showed lower NT-proBNP and BNP levels in the third trimester compared to the first trimester, while one by Furenäs et al showed no differences in NT-proBNP. 15 , 23 , 24 However, these were (N < 300), and in clinical populations that were not racially/ethnically diverse. On the other hand, a recent longitudinal of 307 pregnant women with existing cardiovascular disease showed stable NT-proBNP levels until labor and delivery, when a transient rise occurred, followed again by return to baseline NT-proBNP levels.…”
Section: Discussionmentioning
confidence: 97%